Pengaruh Literasi Keuangan, Kemudahan E-money, dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa (Studi Kasus: Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wiraraja Madura) - sandy, Mutiara ike faradillah; Syam, M. Munir (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Consumptive behavior among university students has become increasingly prominent in the digital era, particularly with the emergence of shopping platforms like TikTok Shop. This study aims to examine the influence of financial literacy, e-money convenience, and lifestyle on the consumptive behavior of students in the Management Study Program at the Faculty of Economics and Business, Wiraraja University Madura. A quantitative approach was employed, targeting a population of 462 active students from the 2021 and 2022 cohorts. Using purposive sampling and the Slovin formula, 83 respondents were selected. Data were collected through questionnaires and analyzed using multiple linear regression via SPSS 25. The findings reveal that, partially, financial literacy and e-money convenience do not have a significant impact on consumptive behavior, while lifestyle shows a significant influence. Simultaneously, the three variables together significantly explain variations in student consumption behavior. These results suggest that despite awareness and ease of digital financial tools, a consumer-oriented lifestyle remains the dominant factor driving student purchasing decisions.